2016
DOI: 10.1039/c6em00093b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different forms of plant-derived organic matter on nitrous oxide emissions

Abstract: To investigate the impact of different forms of plant-derived organic matter on nitrous oxide (N2O) emissions, an incubation experiment with the same rate of total nitrogen (N) application was carried out at 25 °C for 250 days. Soils were incorporated with maize-derived organic matter (i.e., maize residue-derived dissolved organic matter and maize residues with different C/N ratios) and an inorganic N fertilizer (urea). The pattern and magnitude of nitrous oxide (N2O) emissions were affected by the form of N a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
(87 reference statements)
1
3
1
Order By: Relevance
“…Available Online at SAINS TANAH Website : http://jurnal.uns.ac.id/tanah/index SAINS TANAH -Journal of Soil Science and Agroclimatology, 15(1), 2018, 54- Potential production of N2O correlated positively with total organic carbon (TOC) (r=0.87, P<0.001, n=8), humic acid (HA) (r=0.85, P<0.001, n=8), fulvic acid (FA) (r=0.82, P<0.001, n=8) and total nitrogen (TN) (r=0.94,P<0.001,n=8). This result was supported by finding of Qiu, Q., L. Wu, Z. Ouyang (2016) who stated that addition of N-organic fertilizer causes higher N2O emissions than the application of single N-inorganic fertilizer or together with Norganic fertilizers. According to Huang, et al (2004) application of organic matter produced higher N2O emissions than urea.…”
Section: The Relationship Between the Potential Production Of Ch4 Andsupporting
confidence: 63%
“…Available Online at SAINS TANAH Website : http://jurnal.uns.ac.id/tanah/index SAINS TANAH -Journal of Soil Science and Agroclimatology, 15(1), 2018, 54- Potential production of N2O correlated positively with total organic carbon (TOC) (r=0.87, P<0.001, n=8), humic acid (HA) (r=0.85, P<0.001, n=8), fulvic acid (FA) (r=0.82, P<0.001, n=8) and total nitrogen (TN) (r=0.94,P<0.001,n=8). This result was supported by finding of Qiu, Q., L. Wu, Z. Ouyang (2016) who stated that addition of N-organic fertilizer causes higher N2O emissions than the application of single N-inorganic fertilizer or together with Norganic fertilizers. According to Huang, et al (2004) application of organic matter produced higher N2O emissions than urea.…”
Section: The Relationship Between the Potential Production Of Ch4 Andsupporting
confidence: 63%
“…In contrast, other studies have found relationships between CO 2 and N 2 O emissions (Millar and Baggs, 2004) or between N 2 O production and the C/N ratio of plant material being incorporated, with generally higher emissions from plants with low C/N ratios (Kaiser et al, 1998; Baggs et al, 2000). Qiu et al (2016), however, suggested that the C/N ratio was not a good predictor of N 2 O emissions if available soil N was not limited, as was the case in the current study with the addition of urea.…”
Section: Discussioncontrasting
confidence: 57%
“…We were able to distinguish N 2 O emissions derived from urea N and those derived from added plant N by calculating the difference between emissions from the combined urea and plant treatment (ryegrass 600N, kale 600N, turnip leaf 600N, and turnip bulb 600N) and the plant‐only treatment (ryegrass 0N, kale 0N, turnip leaf 0N, and turnip bulb 0N). The addition of plants, without urea, also increased N 2 O emissions, presumably because increased labile C and N from plant cells provided substrate for nitrification and denitrification (Reddy et al, 1982; Baggs et al, 2000; Kuzyakov and Bol, 2006; Qiu et al, 2016). However, this addition of C alone does not explain the significant difference in emissions between the ryegrass treatment and other tissue treatments, as roughly similar C was added for all plant treatments.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 As denitrifying microbes are largely heterotrophs, N2O production is often limited by the availability of metabolizable organic carbon. 3 Both fungi and bacteria participate in N2O production in soils 18 , and therefore their relative contribution to the denitrification process can be affected by land-use and management. Among anthropogenic activities, agriculture has been identified as the largest contributor to global N2O emission, largely due to tillage operations and application of N fertilizers.…”
Section: Introductionmentioning
confidence: 99%